#TITLE_ALTERNATIVE# - ZUZIKA (NIM : 17314031), RIZKA
Based on the background that Indonesia in particular the city of Bandung is a city with a high religious level, the assumption appears that the need for tourism facilities with the concept of application of shari'ah which became the main complement of Muslim tourism activities, especially in berekreasi, beraksaksasi and of course in worship. So the design of Bandung Islamic Village becomes an effort in providing family holiday facility services in the Islamic context. Designing Bandung Islamic Village originated from three main framework in Islam, namely aqidah, syari'ah and akhlak. So many hadiths that explain the importance of the morality of a Muslim, even Prophet Muhammad SAW said "the most perfect believer is the most good morals". Reviewing the importance of morality, the main point of this design is related to Islamic existence. This design is an attempt to internalize the Islamic daily existence so that users undergo Islamic existence without any coercion or marker, by providing psychological experience from conceptual designs based on the Hadiths and Islamic encyclopaedia sources.